2020
DOI: 10.1021/acs.cgd.0c00295
|View full text |Cite
|
Sign up to set email alerts
|

Application of Model-Free and Model-Based Quality-by-Control (QbC) for the Efficient Design of Pharmaceutical Crystallization Processes

Abstract: The design of pharmaceutical crystallization processes is a challenging engineering problem because of the specific and versatile quality requirements of the end-product, amplified by the tight regulatory standards. The current industrial standard for crystallization process design is based on the use of the quality-bydesign (QbD) framework, which relies on factorial design of experiments (DoE). Hence, QbD inherently generates a large number of resource-consuming open loop crystallization experiments. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 44 publications
0
31
0
Order By: Relevance
“…As a result, an operating space of parameters can be defined, and within this processing region (design space) the desired product quality can be reached. As another step forward, the concept of Quality-by-Control (QbC) has been proposed in the recent years . The QbC paradigm takes the QbD approaches to a higher level by applying active feedback control for process design .…”
Section: First Steps Toward Continuous Pharmaceutical Manufacturingmentioning
confidence: 99%
“…As a result, an operating space of parameters can be defined, and within this processing region (design space) the desired product quality can be reached. As another step forward, the concept of Quality-by-Control (QbC) has been proposed in the recent years . The QbC paradigm takes the QbD approaches to a higher level by applying active feedback control for process design .…”
Section: First Steps Toward Continuous Pharmaceutical Manufacturingmentioning
confidence: 99%
“…Model-based predictive control is already very well described in batch crystallization. The number of studies in which the model-based predictive control (MPC) is applied to continuous systems is quite low but has increased significantly over the last two decades. Because of better computing power and improved mathematical model knowledge, even more complex systems can be solved efficiently and with short computing times.…”
Section: Model-based Predictive Control and Process Intensificationmentioning
confidence: 99%
“…Direct nucleation control (DNC) and supersaturation control (SSC) experiments are popular feedback control strategies relying on controlling the relative number density (former) and supersaturation (latter). It has been shown that from an information theory perspective for parameter estimation suboptimal DNC and SSC experiments can be used for improved kinetic parameter estimation . In this case study, the concentration, in-process particle counts as measured by FBRM, and product CSD data of five of these experiments were applied for parameter estimation, listed in Table .…”
Section: Parameter Estimation Case Studies Using Crysivmentioning
confidence: 99%